Level of cardiovascular fitness and it’s relationship with physical activity and body mass index in young adults of Islamabad - Zainab Khatoon; Muhammad Afzaal Afridi; Taqdees-e-Maryam; Afifa Gull; Hania Farheen (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the level of cardiovascular fitness in young adults, and to find the relationship of maximum oxygen uptake with body mass index and physical activity. Methods: The cross-sectional study was conducted at two private universities in Islamabad, Pakistan, from January to June 2019, and comprised subjects of both genders aged 18-25 years with normal cardiopulmonary system. Physical activity was measured usint the short form of International Physical Activity Questionnaire, while maximum oxygen uptake was measured using the Bruce protocol. Data was analysed using SPSS 24. Results: Of the 321 subjects, 59(18.4%) were males and 262(81.6%) were females. The overall mean age was 21.15±1.73 years. Overall, 190(57.3%) subjects had normal body mass index, 86(26.8%) had high level of physical activity, and 85(26.5%) had moderate level. With respect to to maximum oxygen uptake, 28(47.5%) of the males were in the superior category, while 72(27.5%) women were in the good category. All the vitals along with dyspnoea and fatigue showed significant difference (p?0.05) except oxygen saturation (p=0.062). Maximum oxygen uptake showed negative weak (p=0.40) correlation with body mass index, and weak, positive and significant correlation (p=0.007) with physical activity. Conclusion: Majority of the young adults were found to be active as indicated by the levels of their maximum oxygen uptake and physical activity. Significant correlation was found between cardiovascular fitness and physical activity. Continuous...